Biomechanical report for the IAAF World Indoor Championships 2018 long jump women - Tucker, C.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The women`s long jump took place on the afternoon of Sunday 4th March. It was Moguenara-Taroum who was contesting for first place with Ivana Španovic in the first two rounds. However, from round 4 it was a battle between Španovic and the previous World Indoor Champion, Brittney Reese. It was Španovic who emerged victorious with a jump of 6.96 metres defeating Reese into second place. In the end Moguenara-Taroum`s second round effort of 6.85 metres was enough to clinch the bronze medal by four centimetres from Quanesha Burks.